Unamuno and his critique of regional linguistic separatism - Maroco dos Santos, Emanuel José (Resonancias. Revista de Filosofía, 2019)
Unamuno’s critique of linguistic separatism in the rest of Spain’s regions is famous and only too well known. Nonetheless, although his general postulate is known, many of its aspects are not familiar to most interpreters of his thought. In this article we shall try to collect all of the critiques that Unamuno made of Basque, Galician, and Catalan, with a view to understanding his reasons for opposing their establishment as official languages in their respective regions. It is thus an historical-hermeneutical reconstruction of his thought. However, since our goal is not to debate with Unamuno his more polemical linguistic theses, we shall assess them and present what in our view is the great cultural-linguistic mistake that Unamuno made.